P78 Cardiovascular and musculoskeletal phenotypes and the clinical outcomes in copd: a systematic review and meta-analysis. (15th November 2017) - Fermont, JM; Masconi, KL; Wood, AM; Müllerova, H; Wilkinson, IB
Abstract : Systematic reviews examining the relationship between cardiovascular and musculoskeletal phenotypes and relevant clinical outcomes in chronic obstructive pulmonary disease (COPD) are currently lacking. We have systematically summarised and examined the predictive value of selected phenotypes that could be utilised in clinical practice. We identified 61 cohort studies with longitudinal data collection. Meta-analysis indicated that the 6 min walking distance (6 MWD; HR 0.83, 95% CI 0.79 to 0.87), resting heart rate (HR 1.09, 95% CI 1.02 to 1.15), C-reactive protein (HR 1.24, 95% CI 1.08 to 1.40), fibrinogen (HR 4.18, 95% CI 1.13 to 7.22) and tumour necrosis factor-alpha (HR 0.91, 95% CI 0.82 to 1.00) were independent predictors of clinical outcomes in stable COPD patients, after adjusting for sex, age, body mass index and smoking status. Very few studies examined the association between musculoskeletal phenotypes such as the short physical performance battery, quadriceps maximum voluntary contraction, and sniff nasal inspiratory pressure and clinical outcomes in COPD. With the limited adoption of the 6 MWD in clinical practice there is a need for faster and simpler tests to identify COPD patients at an increased risk for adverse events in an early stage of disease.